Transforming silicon slag into high‐capacity anode material for lithium‐ion batteries. Issue 4 (8th August 2022) - Vanpeene, Victor; Heitz, Alexandre; Herkendaal, Natalie; Soucy, Patrick; Douillard, Thierry; Roué, Lionel
Abstract: The conception of cheaper and greener electrode materials is critical for lithium (Li)‐ion battery manufacturers. In this study, a by‐product of the carbothermic reduction of SiO2 to Si, containing 65 wt% Si, 31 wt% SiC, and 4 wt% C, is evaluated as raw material for the production of high‐capacity anodes for Li‐ion batteries. After 20 h of high‐energy ball milling, C is fully converted to SiC and a micrometric powder ( D 50  ∼1 μm) is obtained in which submicrometric SiC inclusions are embedded in a nanocrystalline/amorphous Si matrix. This material is able to maintain a capacity >1000 mAh g −1 (>3 mAh cm −2 ) over 100 cycles. No crystalline Li15 Si4 phase is formed upon cycling as shown from the differential dQ / dV curves. The good mechanical resiliency of the electrode is evidenced by monitoring its morphological changes from sequential focused ion beam scanning electron microscopy analyses. However, a progressive and irreversible increase in the electrode mass and thickness is observed over cycling (reaching 125% and 60% after 200 cycles, respectively), which is mainly attributed to the accumulation of solid electrolyte interphase products in the electrode. Abstract : A by‐product of the carbothermic reduction of SiO2 is valorized as a low‐cost and high‐capacity anode material for Li‐ion batteries. Ball milling of this by‐product results in a micrometric powder where submicrometric SiC inclusions are embedded in a Si matrix. It displays a capacity >1000 mAh g −1 (>3 mAh cm −2 ) over 100 cycles.